The long-term effectiveness of cognitive behavior therapy for psychosis within a routine psychological therapies service - Peters, Emmanuelle; Crombie, Tessa; Agbedjro, Deborah; Johns, Louise C.; Stahl, Daniel; Greenwood, Kathryn; Keen, Nadine; Onwumere, Juliana; Hunter, Elaine; Smith, Laura; Kuipers, Elizabeth (Frontiers in Psychology, 2015)
Randomised Controlled Trials (RCTs) have shown the efficacy of CBTp, however few studies have considered its long-term effectiveness in routine services. This study reports the outcomes of clients seen in a psychological therapies clinic, set up following positive results obtained from an RCT (Peters et al. 2010). The aims were to evaluate the effectiveness of CBTp, using data from the service’s routine assessments for consecutive referrals over a 12 year period, and assess whether gains were maintained at a 6+ months’ follow-up. Of the 476 consenting referrals, all clients (N=358) who received ≥5 therapy sessions were offered an assessment at 4 time points (baseline, pre-, mid- and end of therapy) on measures assessing current psychosis symptoms, emotional problems, general well-being and life satisfaction. A sub-set (N=113) was assessed at a median of 12 months after finishing therapy. Following the waiting list (median of 3 months) clients received individualised, formulation-based CBTp for a median number of 19 sessions from 121 therapists with a range of experience receiving regular supervision. Clients showed no meaningful change on any measure while on the waiting list (Cohen’s d<=0.23). In contrast, highly significant improvements following therapy, all of which were significantly greater than changes during the waiting list, were found on all domains assessed (Cohen’s d: 0.44-0.75). All gains were maintained at follow-up (Cohen’s d: 0.29-0.82), with little change between end of therapy and follow-up (Cohen’s d<=0.18). Drop-out rate from therapy was low (13%). These results demonstrate the positive and potentially enduring impact of psychological therapy on a range of meaningful outcomes for clients with psychosis. The follow-up assessments were conducted on only a sub-set, which may not generalise to the full sample. Nevertheless this study is the largest of its kind in psychosis, and has important implications for the practice of CBTp in clinical services.